Vascular Endothelial Growth Factor–Induced Neovascularization Rescues Cardiac Function But Not Adverse Remodeling at Advanced Ischemic Heart Disease - Gordon, Oren; Gilon, Dan; He, Zhiheng; May, Dalit; Lazarus, Alon; Oppenheim, Amit; Keshet, Eli (Arteriosclerosis, thrombosis, and vascular biology, 2012)
OBJECTIVE—Proangiogenic therapy is a promising avenue for the treatment for chronic heart failure and a potentially powerful modality for reversing adverse cardiac remodeling. There is a concern, however, that adverse remodeling might enter an irreversible stage, and become refractory to treatments. The present study aims to determine whether neovascularization therapy is feasible at end stage heart failure and its capacity to reverse adverse cardiac remodeling during progressive disease stages. METHODS AND RESULTS—Using a conditional transgenic mouse system for generating escalating levels of myocardium-specific vascular deficit and resultant stepwise development of heart remodeling, we show that left ventricular dilatation and fibrosis precede ventricular hypertrophy, but that interstitial fibrosis is progressive and eventually results in heart failure. Vascular endothelial growth factor–mediated neovascularization was efficient even at the end stage of disease, and rescued compromised contractile function. Remarkably, remodeling was also fully reversed by neovascularization during early and late stages. Adverse remodeling could not be rescued, however, at the end stage of the disease, thus defining a point of no return and indentifying a critical level of fibrosis as the key determinant to be considered in intended reversal. CONCLUSION—The study supports the notion of a restricted golden time for remodeling reversal but not for vascular endothelial growth factor–induced neovascularization, which is feasible even during advanced disease stages.